The spatiotemporal changes and influencing mechanisms of the coastline in the Yellow River Delta, China - Yang, Zhuo; Gao, Wei; Yu, Wenjie; Liu, Jie; Du, Jun; Li, Ping; Xu, Yuanqin; Li, Ping (Frontiers in Marine Science, 2025)
Using remote sensing imagery of the Yellow River Delta (YRD) from 1984 to 2024, the Digital Shoreline Analysis System (DSAS) model was employed to analyze the coastline position, migration rate, and characteristics of four typical coastal sections. The response of the coastline changes in the study area to global climate change and human activities was quantitatively assessed. Over the past 40 years, the modern YRD coastline has generally advanced seaward at an average rate of 109.64 m/a. This progression can be divided into three distinct phases: (i) The rapid transition period from 1984 to 2000, during which the total coastline length reached its maximum of nearly 440.65 km in the last 40 years. In 1986, the proportion of artificial coastline surpassed that of natural coastline for the first time. (ii) A decreasing trend in total coastline length characterized the slow transition period from 2000 to 2015. The transition in coastline types continued the trend of the previous period, with artificial coastlines exceeding 90% for the first time in 2015, marking the highest proportion in the past 40 years. (iii) The stable period from 2015 to the present, during which the total coastline length has shown an increasing trend. The artificial coastline has stabilized, while the growth of the natural coastline has been concentrated around the Yellow River estuary. However, the increase in the natural coastline has gradually slowed due to water and sediment regulation projects from 2001. The evolution of the coastline in the YRD has shifted from early control by river diversions to a current primary influence from human-driven land reclamation projects. Coastal changes in the present estuarine sections are mainly controlled by Yellow River water and sediment inflows, while abandoned northern channels experience pronounced effects from extreme weather, such as cold wave-induced winds. Additionally, factors such as sea-level rise due to global climate change and delta subsidence caused by sediment compaction have lowered the relative elevation of the coastline, further accelerating its erosion and retreat. However, these natural factors have had a lesser impact on coastline evolution than river diversions and human activities.